SPEAKING ANXIETY AMONG ENGLISH FOREIGN LANGUAGE LEARNERS (Journal of Human Sciences, 2025)
This study investigates the factors contributing to speaking anxiety among English as a Foreign Language (EFL) learners at Ajdabia University. The research aims to identify how linguistic, individual, and situational factors influence students' speaking anxiety. A quantitative approach was employed, utilizing a questionnaire based on the Foreign Language Classroom Anxiety Scale (FLCAS), with 100 students participating. The findings reveal that situational and individual factors have the most significant impact on anxiety, while linguistic factors contribute to a lesser extent. Anxiety levels also vary according to gender and semester, with female students and first-year students experiencing higher anxiety. The study suggests that creating a supportive classroom environment and addressing individual emotional factors can help reduce speaking anxiety and improve students' language performance.